"European Resuscitation Council 2015 burn 1st Aid recommendations–concerns and issues for first responders". Issue 5 (August 2016) - Goodwin, Nicholas S.
Abstract: As the lead author of a recently published systematic review on hydrogel burn dressings in pre-hospital, I was alarmed to read the claim by the authors to the effect no one method of burn wound cooling was superior to any other; "There is no evidence to recommend a specific temperature or method of cooling". The reputation and prominence of the ERC within the circle of resuscitation councils now delving into 1st Aid recommendations leads to the conclusion that misguided recommendations may cause confusion amongst first responders, may falsely misdirect 1st Aid providers to unsupported practices or alternatively create a window of opportunity for marketers or sellers of alternative burn 1st Aid technologies to make unsupported claims in respect of comparable efficacy of their own product versus "traditional" methods.